144 A modeling framework to assess the impact of the texas beef cattle water footprint on livestock sustainability. (5th December 2019) - Menendez, Hector M; Turner, Benjamin L; Tedeschi, Luis O
Abstract: Anticipated growth in the demand for beef products driven by increased protein consumption, brings into question the efficiency, sustainability, profitability, and social dimensions of water use for U.S. beef production. Current assessment of U.S. beef production provides a wide range (695 to 14, 191 L H2 O/kg) of water footprint (WF) measurements of green (rainfed), blue (ground or surface), and grey (waste treatment) water use, but lacks defined region-specific estimates. The objective of this ongoing study is to develop a dynamic mathematical model for Texas beef cattle WF (TXWFB ) that allows users to estimate a Texas WF, evaluate assumptions and parameters of current WF methodologies, identify water-use inefficiencies, and provide policy recommendations for a sustainable WF. The TXWFB was developed using Vensim DSS™ and evaluated with the Model Evaluation System™. The TXWFB model correctly replicated the previously published Chapagain and Hoekstra (2003; CH2003) water footprint results for beef cattle with a 36-month lifespan in both grazing [11, 915 m 3 /t (0.4 t)] and industrial beef cattle [9636 m 3 /t (0.545 t)] systems. Then, parameters (diet composition and water footprints) from the CH2003 model were used as inputs into the TXWFB model to develop baseline scenarios for Texas, using ten climate regions (36-month lifespan; baseline grazing µ = 26, 389 m 3 /t and industrial µ = 24, 615 m 3 /t). The baseline results were then compared to grazing and industrial scenarios with regionalized Texas parameters for pasture, forage, and crop production (evapotranspiration, drought), diet/phase/region (cow-calf, stocker, and feedlot; 24 months). The TXWFB predictions for regional grazing (µ = 7, 591 m 3 /t) and industrial (µ = 5, 948 m 3 /t) results were 71 to 75% less than the baseline scenarios (P < 0.05). We concluded that the TXWFB estimates were considerably smaller than those previously published, suggesting that current WF methodologies can be refined to more adequately assess beef cattle WF in the US.